Dual-functional hydrogel system for spinal cord regeneration with sustained release of arylsulfatase B alleviates fibrotic microenvironment and promotes axonal regeneration - Park H.H.; Kim, Young Min; Anh Hong L.T.; Kim H.S.; Sung Hoon Kim; Jin X.; Hwang D.H.; Kwon M.J.; Song, Soo Chang; Kim B.G. (Pergamon Press Ltd., 2022)
Traumatic damage to the spinal cord does not spontaneously heal, often leading to permanent tissue defects. We have shown that injection of imidazole-poly(organophosphazene) hydrogel (I-5) bridges cystic cavities with the newly assembled fibronectin-rich extracellular matrix (ECM). The hydrogel-created ECM contains chondroitin sulfate proteoglycans (CSPGs), collagenous fibrils together with perivascular fibroblasts, and various fibrotic proteins, all of which could hinder axonal growth in the matrix. In an in vitro fibrotic scar model, fibroblasts exhibited enhanced sensitivity to TGF-β1 when grown on CSPGs. To alleviate the fibrotic microenvironment, the I-5 hydrogel was equipped with an additional function by making a complex with ARSB, a human enzyme degrading CSPGs, via hydrophobic interaction. Delivery of the I-5/ARSB complex significantly diminished the fibrotic ECM components. The complex promoted serotonergic axonal growth into the hydrogel-induced matrix and enhanced serotonergic innervation of the lumbar motor neurons. Regeneration of the propriospinal axons deep into the matrix and to the lumbar spinal cord was robustly increased accompanied by improved locomotor recovery. Therefore, our dual-functional system upgraded the functionality of the hydrogel for spinal cord regeneration by creating ECM to bridge tissue defects and concurrently facilitating axonal connections through the newly assembled ECM.